| library; |
| import self as self; |
| import "dart:core" as core; |
| |
| extension Extension1<T extends core::Object*> on T* { |
| method method1 = self::Extension1|method1; |
| tearoff method1 = self::Extension1|get#method1; |
| method method2 = self::Extension1|method2; |
| tearoff method2 = self::Extension1|get#method2; |
| method method3 = self::Extension1|method3; |
| tearoff method3 = self::Extension1|get#method3; |
| method method4 = self::Extension1|method4; |
| tearoff method4 = self::Extension1|get#method4; |
| } |
| extension Extension2<T extends core::String*> on T* { |
| method method1 = self::Extension2|method1; |
| tearoff method1 = self::Extension2|get#method1; |
| method method2 = self::Extension2|method2; |
| tearoff method2 = self::Extension2|get#method2; |
| method method3 = self::Extension2|method3; |
| tearoff method3 = self::Extension2|get#method3; |
| method method4 = self::Extension2|method4; |
| tearoff method4 = self::Extension2|get#method4; |
| } |
| extension Extension3<T extends dynamic> on T* { |
| method method1 = self::Extension3|method1; |
| tearoff method1 = self::Extension3|get#method1; |
| method method2 = self::Extension3|method2; |
| tearoff method2 = self::Extension3|get#method2; |
| method method3 = self::Extension3|method3; |
| tearoff method3 = self::Extension3|get#method3; |
| method method4 = self::Extension3|method4; |
| tearoff method4 = self::Extension3|get#method4; |
| } |
| extension Extension4<T extends core::Object* = dynamic> on T* { |
| method method1 = self::Extension4|method1; |
| tearoff method1 = self::Extension4|get#method1; |
| method method2 = self::Extension4|method2; |
| tearoff method2 = self::Extension4|get#method2; |
| method method3 = self::Extension4|method3; |
| tearoff method3 = self::Extension4|get#method3; |
| method method4 = self::Extension4|method4; |
| tearoff method4 = self::Extension4|get#method4; |
| } |
| static method Extension1|method1<T extends core::Object*, S extends core::Object*>(lowered final self::Extension1|method1::T* #this) → dynamic |
| ; |
| static method Extension1|get#method1<T extends core::Object*>(lowered final self::Extension1|get#method1::T* #this) → <S extends core::Object*>() →* dynamic |
| return <S extends core::Object*>() → dynamic => self::Extension1|method1<self::Extension1|get#method1::T*, S*>(#this); |
| static method Extension1|method2<T extends core::Object*, S extends core::String*>(lowered final self::Extension1|method2::T* #this) → dynamic |
| ; |
| static method Extension1|get#method2<T extends core::Object*>(lowered final self::Extension1|get#method2::T* #this) → <S extends core::String*>() →* dynamic |
| return <S extends core::String*>() → dynamic => self::Extension1|method2<self::Extension1|get#method2::T*, S*>(#this); |
| static method Extension1|method3<T extends core::Object*, S extends dynamic>(lowered final self::Extension1|method3::T* #this) → dynamic |
| ; |
| static method Extension1|get#method3<T extends core::Object*>(lowered final self::Extension1|get#method3::T* #this) → <S extends dynamic>() →* dynamic |
| return <S extends dynamic>() → dynamic => self::Extension1|method3<self::Extension1|get#method3::T*, S%>(#this); |
| static method Extension1|method4<T extends core::Object*, S extends core::Object* = dynamic>(lowered final self::Extension1|method4::T* #this) → dynamic |
| ; |
| static method Extension1|get#method4<T extends core::Object*>(lowered final self::Extension1|get#method4::T* #this) → <S extends core::Object* = dynamic>() →* dynamic |
| return <S extends core::Object* = dynamic>() → dynamic => self::Extension1|method4<self::Extension1|get#method4::T*, S*>(#this); |
| static method Extension2|method1<T extends core::String*, S extends core::Object*>(lowered final self::Extension2|method1::T* #this) → dynamic |
| ; |
| static method Extension2|get#method1<T extends core::String*>(lowered final self::Extension2|get#method1::T* #this) → <S extends core::Object*>() →* dynamic |
| return <S extends core::Object*>() → dynamic => self::Extension2|method1<self::Extension2|get#method1::T*, S*>(#this); |
| static method Extension2|method2<T extends core::String*, S extends core::String*>(lowered final self::Extension2|method2::T* #this) → dynamic |
| ; |
| static method Extension2|get#method2<T extends core::String*>(lowered final self::Extension2|get#method2::T* #this) → <S extends core::String*>() →* dynamic |
| return <S extends core::String*>() → dynamic => self::Extension2|method2<self::Extension2|get#method2::T*, S*>(#this); |
| static method Extension2|method3<T extends core::String*, S extends dynamic>(lowered final self::Extension2|method3::T* #this) → dynamic |
| ; |
| static method Extension2|get#method3<T extends core::String*>(lowered final self::Extension2|get#method3::T* #this) → <S extends dynamic>() →* dynamic |
| return <S extends dynamic>() → dynamic => self::Extension2|method3<self::Extension2|get#method3::T*, S%>(#this); |
| static method Extension2|method4<T extends core::String*, S extends core::Object* = dynamic>(lowered final self::Extension2|method4::T* #this) → dynamic |
| ; |
| static method Extension2|get#method4<T extends core::String*>(lowered final self::Extension2|get#method4::T* #this) → <S extends core::Object* = dynamic>() →* dynamic |
| return <S extends core::Object* = dynamic>() → dynamic => self::Extension2|method4<self::Extension2|get#method4::T*, S*>(#this); |
| static method Extension3|method1<T extends dynamic, S extends core::Object*>(lowered final self::Extension3|method1::T* #this) → dynamic |
| ; |
| static method Extension3|get#method1<T extends dynamic>(lowered final self::Extension3|get#method1::T* #this) → <S extends core::Object*>() →* dynamic |
| return <S extends core::Object*>() → dynamic => self::Extension3|method1<self::Extension3|get#method1::T%, S*>(#this); |
| static method Extension3|method2<T extends dynamic, S extends core::String*>(lowered final self::Extension3|method2::T* #this) → dynamic |
| ; |
| static method Extension3|get#method2<T extends dynamic>(lowered final self::Extension3|get#method2::T* #this) → <S extends core::String*>() →* dynamic |
| return <S extends core::String*>() → dynamic => self::Extension3|method2<self::Extension3|get#method2::T%, S*>(#this); |
| static method Extension3|method3<T extends dynamic, S extends dynamic>(lowered final self::Extension3|method3::T* #this) → dynamic |
| ; |
| static method Extension3|get#method3<T extends dynamic>(lowered final self::Extension3|get#method3::T* #this) → <S extends dynamic>() →* dynamic |
| return <S extends dynamic>() → dynamic => self::Extension3|method3<self::Extension3|get#method3::T%, S%>(#this); |
| static method Extension3|method4<T extends dynamic, S extends core::Object* = dynamic>(lowered final self::Extension3|method4::T* #this) → dynamic |
| ; |
| static method Extension3|get#method4<T extends dynamic>(lowered final self::Extension3|get#method4::T* #this) → <S extends core::Object* = dynamic>() →* dynamic |
| return <S extends core::Object* = dynamic>() → dynamic => self::Extension3|method4<self::Extension3|get#method4::T%, S*>(#this); |
| static method Extension4|method1<T extends core::Object* = dynamic, S extends core::Object*>(lowered final self::Extension4|method1::T* #this) → dynamic |
| ; |
| static method Extension4|get#method1<T extends core::Object* = dynamic>(lowered final self::Extension4|get#method1::T* #this) → <S extends core::Object*>() →* dynamic |
| return <S extends core::Object*>() → dynamic => self::Extension4|method1<self::Extension4|get#method1::T*, S*>(#this); |
| static method Extension4|method2<T extends core::Object* = dynamic, S extends core::String*>(lowered final self::Extension4|method2::T* #this) → dynamic |
| ; |
| static method Extension4|get#method2<T extends core::Object* = dynamic>(lowered final self::Extension4|get#method2::T* #this) → <S extends core::String*>() →* dynamic |
| return <S extends core::String*>() → dynamic => self::Extension4|method2<self::Extension4|get#method2::T*, S*>(#this); |
| static method Extension4|method3<T extends core::Object* = dynamic, S extends dynamic>(lowered final self::Extension4|method3::T* #this) → dynamic |
| ; |
| static method Extension4|get#method3<T extends core::Object* = dynamic>(lowered final self::Extension4|get#method3::T* #this) → <S extends dynamic>() →* dynamic |
| return <S extends dynamic>() → dynamic => self::Extension4|method3<self::Extension4|get#method3::T*, S%>(#this); |
| static method Extension4|method4<T extends core::Object* = dynamic, S extends core::Object* = dynamic>(lowered final self::Extension4|method4::T* #this) → dynamic |
| ; |
| static method Extension4|get#method4<T extends core::Object* = dynamic>(lowered final self::Extension4|get#method4::T* #this) → <S extends core::Object* = dynamic>() →* dynamic |
| return <S extends core::Object* = dynamic>() → dynamic => self::Extension4|method4<self::Extension4|get#method4::T*, S*>(#this); |
| static method main() → dynamic |
| ; |